FUNCTIONAL DISORDERS OF THE DIGESTIVE ORGANS IN EARLY CHILDREN REGURGITATION - Saidullo Kurbanovich Rasulov (Galaxy International Interdisciplinary Research Journal, 2024)
The goal is to focus medical practitioners’ attention on regurgitation, which is common in young children, and to increase their knowledge in this area through wider implementation. The article describes regurgitation, its epidemiology, classification, etiology, pathogenetic factors, clinical picture, diagnosis, differential diagnosis based on Roman criteria and modern recommendations, as well as dietary treatment methods, medicinal milk formulas and other treatment methods.